3D visualization of uterus and ovary: tissue clearing techniques and biomedical applications - Liu, Qiqi; Song, Zhuo; Liu, Simin; Dong, Zirui; Zheng, Xi; Leung, Tak Yeung; Chen, Xiaoyan (Frontiers in Bioengineering and Biotechnology, 2025)
Recent advancements in tissue clearing and three-dimensional (3D) visualization technologies have enabled subcellular-level examination of entire organs, particularly in complex structures such as the ovary and uterus. Traditional histological approaches are limited by two-dimensional views, which restrict our understanding of female reproductive system functions. In this review, we highlight the innovations in 3D tissue clearing techniques applied to uterine and ovarian tissues, which, combined with analytical tools, facilitate comprehensive 3D visualization and image analysis. We evaluate the advantages and disadvantages of three primary categories of tissue clearing techniques: organic solvent-based, hydrogel-based, and hydrogel-embedded methods, specifically regarding the uterus and ovary. Light-sheet and multiphoton microscopy complement these techniques, providing unprecedented capabilities for high-resolution imaging of large tissue volumes. Tissue clearing technologies provide a robust strategy for early diagnosis of uterine and ovarian pathologies. Additionally, we explore the integration of tissue clearing technologies with spatial transcriptomics and AI-driven analytical tools to achieve comprehensive 3D molecular mapping. We hope this review contributes to a better understanding of tissue clearing techniques and can help researchers in navigating methodological choices for uterine and ovarian investigations.